Potential Effect of Leukocyte-Platelet-Rich Fibrin in Bone Healing of Skull Base: A Pilot Study. (16th November 2017) - Fredes, Felipe; Pinto, Jaime; Pinto, Nelson; Rojas, Pablo; Prevedello, Daniel M.; Carrau, Ricardo L.; Schmidt, Thomas
Abstract : Background . Reconstruction of surgical defects following cranial base surgery is challenging. Others have demonstrated that leukocyte-platelet-rich fibrin (L-PRF) stimulates tissue healing and bone regeneration. However, these studies have addressed mostly maxillofacial surgical wounds. Objective . The objective of this study was to assess the possible adjuvant role of L-PRF in inducing neoossification of the surgical bone defect in anterior skull base surgery. Methods . We identified patients who had undergone an endoscopic endonasal surgery of the anterior skull base in which L-PRF membranes were used for the reconstruction of the bone defect and who were followed up with postoperative CT scans. CT findings were then correlated with baseline scans and with the CT scans of a patient who had undergone imaging and histologic analysis after maxillofacial surgery in which L-PRF was used and in which we demonstrated bone formation. Results . Five patients fulfilled the inclusion criteria. In four patients, the CT scan demonstrated closure of the bony defect by neoosteogenesis; however, the bone appeared less dense than the surrounding normal bone. A comparison with the control patient yielded similar radiological features. Conclusion . This case series suggests that L-PRF may induce bone healing and regeneration at the surgical site defect. Multi-institutional studies with a larger series of patients are required to confirm this possibility.